P570 Prediction of achieving remission in Crohn's disease patients by abdominal Imaging. (27th May 2021) - Meringer, H; Tzadok, R; Mercer, D; Handler, M; Barnes, S; Waterman, M; Abadi, S; Margalit Yehuda, R; Kopylov, U; Amitai, M M; Bar-Gil Shitrit, A; Sheynkman, G; et al.
Abstract: Background: Vedolizumab (VDZ) is an effective therapy in patients with Crohn's disease (CD). Early prediction of response remains an unmet need. We aimed to evaluate whether abdominal imaging can predict response to VDZ. Methods: Abdominal imaging [Computed tomography enterography (CTE) or magnetic resonance enterography (MRE)] of CD patients initiating therapy with VDZ was evaluated, up to 4 months before VDZ initiation. Response to VDZ was determined at week 26 using the Harvey–Bradshaw index (HBI) or the Crohn's Disease Activity Index (CDAI), in cases no objective score was available it was defined based on the physician assessment. Results: Thirty-three CD patients were included. At week 26, clinical response and remission were achieved in 20(60.6%) and 14(42.4%) patients, respectively. CRP and Calprotectin levels were available for 22/33 and 7/33 patients at week 26. As expected, levels trended lower in remission versus no remission- median CRP 2.41mg/L [IQR 1.3–4.5] vs 10.2[1.6–44.6], p=0.11 and 23.5 µg/g [5–42] vs 2002.8[191–2003], p=0.095, though this did not reach statistical significance. Clinical remission versus no remission was significantly associated with being biologic naïve, 8/14 vs 2/19 (p=0.01) and no prior CD surgeries, 10/14 vs 6/19 (p=0.04). Characteristics of local inflammation as mural edema, fibrofatty proliferation or lymphadenopathy were higher in patients achieving remission versus non-remission. The presence of either mural edema or fibro-fatty proliferation was significantly associated with remission (12/14 vs 9/19, p=0.03). The presence of stenosis in imaging was nominally higher in patients failing to achieve remission (14/19 vs 6/14, p=0.15). Number of diseased segments, length of inflammation or the maximal bowel thickness were similar in remission and no-remission. Conclusion: Baseline imaging may help to predict remission based on the presence of either mural edema or fibrofatty proliferation and the absence of stenosis